Peningkatan Kapasitas Pemasaran Digital bagi Pelaku UMKM di Perumnas Monang Maning Denpasar Barat - Iis Noviyanti; Riri Oktarini; Nurmin Arianto (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
The community service program aimed to enhance the digital marketing capacity of micro, small, and medium enterprise (MSME) entrepreneurs in Perumnas Monang Maning, West Denpasar. This initiative was motivated by the limited understanding and application of digital marketing strategies among local MSME actors, which hindered their competitiveness in the digital economy. The program sought to strengthen participants’ abilities to promote products and services through online platforms effectively. The activity was conducted on October 25–26, 2025, in Perumnas Monang Maning, involving ten lecturers from Universitas Pamulang as facilitators and twenty-four local residents as participants. The implementation methods included lectures, hands-on practice, group discussions, and question-and-answer sessions. The PKM process consisted of three stages: preparation, implementation, and reporting. The results indicated a significant improvement in participants’ knowledge and practical skills in digital marketing, particularly in creating social media content, managing online promotions, and developing simple digital catalogs. Furthermore, participants reported increased confidence in using digital tools to expand their business networks and customer reach. Overall, the program effectively contributed to empowering local MSMEs to adopt sustainable digital marketing strategies.